Corrosion of WC-VC-Co Hardmetal in Neutral Chloride Containing Media. (29th January 2013) - Machio, C. N.; Konadu, D. S.; Potgieter, J. H.; Potgieter-Vermaak, S.; Van der Merwe, J.
Abstract : The effect of varying VC content on the corrosion behavior of WC-10 wt% Co hardmetals in sodium chloride (NaCl) and synthetic mine water (SMW) solutions has been investigated using anodic polarization scans and surface analytical methods. It is shown that the polarization behavior is active-pseudopassive in NaCl and active in SMW regardless of the VC content, while the corrosion resistance is poorer and independent of VC content in NaCl but better at high VC contents in SMW. The corrosion behavior of samples is explained using the effect of VC on the chemical composition of the binder.